The Ecological Validity of Research Studies on Function-Based Interventions in Schools for Children With Autism Spectrum Disorder. Issue 1 (January 2022) - Chezan, Laura C.; McCammon, Meka N.; Drasgow, Erik; Wolfe, Katie
Our main purpose in this review was to determine the extent to which ecological validity was demonstrated and assessed in single-case experimental design (SCED) studies examining the effectiveness of function-based interventions (FBIs) for children with autism spectrum disorder (ASD) within schools. We reviewed 55 SCED studies published between 1985 and 2019 to identify indicators of ecological validity and the instruments used to assess it. We also conducted an analysis to determine the extent to which implementation procedures were described. Results indicated that approximately half of the assessments and FBIs were conducted by teachers in classrooms. Approximately 50% of the assessments and FBIs were implemented within the context of isolated sessions and required multiple implementers. Ecological validity was assessed in seven of the studies reviewed. A complete description of implementation procedures was provided for approximately half of the assessments and FBIs. Limitations of the present review and future directions for research are discussed.